KONSTRUKSI UNSUR DELIK PENIPUAN DAN KECUKUPAN PERTANGGUNGJAWABAN PIDANA DALAM DUGAAN PENYALAHGUNAAN DANA UMRAH: STUDI NORMATIF-EMPIRIS ATAS KASUS SLV TRAVEL DI MAKASSAR - Amran, Amran (Gapenas Publisher, 2025)
Umrah as a religious activity with high spiritual value has grown rapidly alongside increasing public demand for religious travel services in Indonesia. However, the expansion of this industry has not always been accompanied by adequate governance and supervision, leading to alleged misuse of pilgrims’ funds that may be legally classified as fraud. This study addresses three main questions: (1) how the elements of “deceit” and “a series of lies” are constructed in the alleged fraud of SLV Travel under Article 378 of the Indonesian Criminal Code (KUHP); (2) whether the criminal liability framework in the KUHP and Law Number 8 of 2019 on the Implementation of Hajj and Umrah is sufficient to ensure legal protection and recovery of victims’ rights; and (3) what legal implications and policy recommendations can strengthen prevention and law enforcement mechanisms. Using a normative-empirical approach, the study finds that doctrinally the pattern of conduct in the SLV Travel case potentially fulfills the elements of fraud under Article 378 KUHP. Nevertheless, although the punitive framework is adequate to prosecute offenders, the system remains predominantly retributive and has not optimally ensured effective victim compensation. The novelty of this research lies in its analysis of the construction of fraud elements at the pre-adjudicative stage and its integrative evaluation of criminal law and sectoral umrah regulation. Its contribution is the proposal of a preventive–repressive model oriented toward victim protection through risk-based supervision, segregation of pilgrims’ funds, and the integration of restitution within criminal proceedings.